Operating principle and indications for the use of Ranisilver - Banasiewicz, Tomasz (Lekarz POZ, 2018)
Wound healing is a complex and multistage process. The optimal strategy of treatment should stimulate all healing phases and strive to achieve the best healing effect, both in functional and visual terms. Ranisilver is a complex product containing hyaluronic acid, micronised silver, acacia phytocollagen, vitamin E, and vegetable oils. All these components have a beneficial effect on wound healing, tissue regeneration, and optimal therapeutic effect. Particularly important is the action allowing a proper wound environment (moisture) and rapid skinning (epithelialisation). The preparation can be used in many types of acute and chronic wounds, including the treatment of postoperative wounds, burns, skin damage (abrasions, irritation), and wound healing after proctology procedures.